Feasibility Analysis of VCO Conventional Production Process - Anwardi, Anwardi; Abdillah, Hafiz; Kusumanto, Ismu; Harpito, Harpito (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2024)
The economic uncertainty of the Inhil community is influenced by the fluctuating coconut price, which is the main source of income. This uncertainty necessitates derivative products that can be made and processed easily, such as Virgin Coconut Oil (VCO). Many types of VCO have been marketed, and produced from different raw materials. Therefore, this study aimed to analyze the feasibility of conventional VCO production businesses and examine sensitive indicators from each aspect. Business feasibility analysis parameters include market and marketing, technical, management and human resources (HR), legal, and financial aspects. Feasibility index was calculated using the Multi-Dimensional Scaling (MDS) method and all aspects were declared feasible. The feasibility index for each aspect showed a score of 53.28%, 60.91%, 65%, 40%, and 74.83% for technical, manager, HR, legal, and financial aspects, respectively, with a general score of 83.50%.